Features of the formation of land plots for servicing utility buildings and road transport structures - Kustovska, O.; Verteletskyi, O.; Rudenko, A. (Land Management, Cadastre and Land Monitoring, 2021)
The article examines the process of forming land plots for the maintenance of farm buildings and structures of road transport. It is substantiated that the specifics of the category of land for industry, transport, communications, energy, defense and other purposes is that their formation as an independent category of land is largely due to the withdrawal or redemption of land from agricultural or forestry production.The peculiarities of allotment of land plots for commercial use, in particular, land plots for servicing of economic buildings and constructions of motor transport are substantiated. The stages of construction of road transport facilities and the list of documents that the project customer, in addition to the design assignment, provides to the project organization. Rationale for the formation of land for maintenance of commercial buildings and structures of road transport was considered in the Pryluky district of Chernihiv region.Keywords: land, construction and maintenance, buildings and structures of road transport, rent, permanent use.